MEDIA PEMBELAJARAN DIGITAL DALAM PENDIDIKAN BAHASA ARAB ANALISIS MANFAAT PELUANG DAN TANTANGAN KAJIAN LITERATUR - Fatima Azzahrah; Suci Amaliah; Zahratunnisa; Abd.Wahab; Satria; Sudirman; Kamus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid advancement of digital technology has significantly transformed various sectors of human life, including education. In the context of Arabic language education, the integration of digital learning media has become a strategic approach to improving the quality of teaching and learning processes that align with the characteristics of twenty-first-century learners. Nevertheless, the implementation of digital learning media in Arabic language education continues to encounter several challenges, including limited digital competence among educators, unequal access to technological resources, and the underutilization of innovative and interactive learning media. This study aims to analyze the forms of digital learning media utilized in Arabic language education, examine their roles and benefits in supporting the learning process, and identify the opportunities and challenges associated with their implementation in the digital era. This research employed a qualitative approach using a library research method. Data were collected through documentation studies of relevant literature, including journal articles, books, research reports, and other academic sources, and were analyzed using content analysis techniques. The findings indicate that the most commonly utilized digital learning media in Arabic language education include audiovisual media, mobile-based learning applications, Learning Management Systems (LMS), educational social media platforms, and gamification-based learning tools. These media contribute significantly to enhancing students' learning motivation, improving Arabic language skills, expanding access to learning resources, and creating more flexible, interactive, and student-centered learning environments. However, their implementation remains constrained by inadequate technological infrastructure, limited digital literacy among educators, and the potential for digital distractions. Therefore, comprehensive support through educational policies, continuous professional development for educators, and the development of innovative digital learning media is essential to optimize the quality and effectiveness of Arabic language education in the digital era.